Worst case analysis of a simple routing problem - Cruz, R.L.; Chuah, M.C. (Proceedings of the 28th IEEE Conference on Decision and Control, 1989)
A simple routing problem in which there are two service stations is considered. Subject to burstiness constraints on the arrival of work, a study is made of the worst-case delay performance of dynamic routing algorithms. Under a light loading condition, it is found that the well-known route-to-shortest (RTS) rule is optimal in some sense. On the other hand, it is shown that under a heavy loading condition, the RTS is not optimal. The performance of RTS routing is compared with that of fixed routing, and other heuristic dynamic routing rules are considered.< >